Seroepidemiology of Pertussis in a Set of Under One Year Old Iranian Children - Ali Badamchi; Seyed Davar Siadat; Fereshteh Shahcheraghi (Vaccine Research, 2019)
Introduction: Pertussis or whooping cough is one of the vaccine preventable diseases. The purpose of this study was to evaluate the seroepidemiology of pertussis in two groups of children (i.e. under 2 months and 2-12 months old) who had been admitted to Tehran Children Hospital. Methods: Sampling from the children was done along with completing a questionnaire including demographic information, clinical symptoms and the history of the parents coughing. The levels of IgG-Ptx antibody were then measured using the children's sera. Results: Overall, 10.8% of the children were not immune, 78.3% were immune, and 10.9% had recent pertussis infections. Moreover, 19.4% of the female and 13.1% of the male subjects had the infection. In the age group less than two months, 16.6% were infected. The likelihood of new infection among the children less than 2 months old was 1.2 times higher than the control group (P < 0.004). Fifty percent of the children who were diagnosed with cyanosis in their clinical examinations had a recent infection (P <0.001).  Conclusion: Pertussis appears to be endemic in Iran with children under one year old being at high risk of the infection. In this regard, maternal vaccination against pertussis for conferring passive immunity to the newborns could be considered as a protection measure.